2015
DOI: 10.1063/1.4930980
|View full text |Cite
|
Sign up to set email alerts
|

Study of SiO2/4H-SiC interface nitridation by post-oxidation annealing in pure nitrogen gas

Abstract: An alternative and effective method to perform interface nitridation for 4H-SiC metal-oxide-semiconductor (MOS) devices was developed. We found that the high-temperature post-oxidation annealing (POA) in N2 ambient was beneficial to incorporate a sufficient amount of nitrogen atoms directly into thermal SiO2/SiC interfaces. Although N2-POA was ineffective for samples with thick thermal oxide layers, interface nitridation using N2-POA was achieved under certain conditions, i.e., thin SiO2 layers (< 15 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…The nitrogen reference is chosen because nitridation is produced through N 2 or NO during POA processes. [1,2,20,21] Additionally, other reference chemical potential choices (e.g., N and O) that could impact our results are discussed in the Supplementary Material. [41]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrogen reference is chosen because nitridation is produced through N 2 or NO during POA processes. [1,2,20,21] Additionally, other reference chemical potential choices (e.g., N and O) that could impact our results are discussed in the Supplementary Material. [41]…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] Easily grown interfaces with the SiC native oxide, SiO 2 , can present a high density of interface states that largely degrade the performance of power devices by reducing carrier mobility and changing the threshold voltage. [3][4][5][6] The improved carrier mobilities after post-oxidation annealing (POA) of 4H-SiC/SiO 2 interfaces in N-rich conditions (N 2 , NO, or N 2 O) [1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or combined oxidation/annealing [22,23] have led to the adoption of the nitridation process in the production of SiC power electronics applications. The underlying mechanism of this process, however, is still elusive despite the considerable efforts made to date in modeling these interfaces, [24][25][26][27][28][29] with suggested mechanisms ranging from the healing of dangling bonds to the removal of interstitial C atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the oxidation temperature, the interface nitridation was likely to be enhanced. 25 A modification was employed in this work by introducing nitrogen as a carrier gas during the wet oxidation process, which has not been reported thus far to minimize the interfacial layer formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study would also make use of the advantage of nitrogen, following the reported studies pertaining to interface nitridation method for 4H-SiC-based MOS devices during postoxidation annealing in pure nitrogen gas, in which the presence of a sufficient amount of nitrogen at the SiO 2 /4H-SiC interface could passivate slow traps at the interface. Depending on the oxidation temperature, the interface nitridation was likely to be enhanced . A modification was employed in this work by introducing nitrogen as a carrier gas during the wet oxidation process, which has not been reported thus far to minimize the interfacial layer formation.…”
Section: Introductionmentioning
confidence: 99%